2010
DOI: 10.2174/157340310793566145
|View full text |Cite
|
Sign up to set email alerts
|

Role of Differential Signaling Pathways and Oxidative Stress in Diabetic Cardiomyopathy

Abstract: Diabetes mellitus increases the risk of heart failure independently of underlying coronary artery disease, and many believe that diabetes leads to cardiomyopathy. The underlying pathogenesis is partially understood. Several factors may contribute to the development of cardiac dysfunction in the absence of coronary artery disease in diabetes mellitus. There is growing evidence that excess generation of highly reactive free radicals, largely due to hyperglycemia, causes oxidative stress, which further exacerbate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 143 publications
(211 reference statements)
3
55
0
1
Order By: Relevance
“…Increase in oxidative stress-derived inflammation has been hypothesized to be a major mechanism in the pathogenesis and progression of type 2 diabetes (13). Studies have shown that an enhancement in oxidative stress jeopardizes function and structure of myocardium through mechanisms such as microvascular injury, abnormalities in calcium homeostasis, and endothelial dysfunction (40). In this study, we observed that voluntary exercise prevented an increase in myocardial lipid peroxidation and attenuated a decrease in antioxidant enzymes' activity in type 2 diabetic rats.…”
Section: Discussionsupporting
confidence: 49%
“…Increase in oxidative stress-derived inflammation has been hypothesized to be a major mechanism in the pathogenesis and progression of type 2 diabetes (13). Studies have shown that an enhancement in oxidative stress jeopardizes function and structure of myocardium through mechanisms such as microvascular injury, abnormalities in calcium homeostasis, and endothelial dysfunction (40). In this study, we observed that voluntary exercise prevented an increase in myocardial lipid peroxidation and attenuated a decrease in antioxidant enzymes' activity in type 2 diabetic rats.…”
Section: Discussionsupporting
confidence: 49%
“…Therefore, excessive ROS represent critical and central mediators of the complicated cascades associated with myocardial cell apoptosis in the setting of DCM. It is believed that hyperglycemia either directly or indirectly participates in ROS production via glucose autoxidation, alterations in the sorbitol (polyol) pathway, the formation of advanced glycation end products (AGEs), and the activation of both protein kinase C (PKC) and nicotinamide adenine dinucleotide phosphate (NADPH)-oxidase [42,43] . More importantly, a previous in vitro study demonstrated that high glucose concentrations induce TLR-4 expression via PKC by stimulating NADPH oxidase [44] .…”
Section: Discussionmentioning
confidence: 99%
“…Lipid overload results in the accumulation of lipid intermediates, such as diacylglycerol (DAG), which activate protein kinase C (PKC) [4] and the production of reactive oxygen species (ROS) [5,6], which can promote apoptosis [7]. Activation of PKC, oxidative stress and myocardial apoptosis are implicated in diabetes-induced cardiovascular complications [8,9].…”
Section: Introductionmentioning
confidence: 99%